Rekonstruksi Prioritas Dana Desa: Adaptasi Pemerintah Desa dalam Perencanaan dan Penganggaran - Vanni Anggara; Nefa Wahyuning Anggraini; Wendi Aji Saputra (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the politics of village fund priority setting by examining how village governments adapt when priorities established in the Village Government Work Plan (RKP Desa) encounter budget constraints, regulations governing the use of Village Funds, external policy agendas, and actor preferences in the preparation of the Village Budget (APB Desa). The study employs a qualitative approach with a case study design in Mardiharjo Village, Purwodadi District, Musi Rawas Regency. Data were collected through an analysis of RKP Desa and APB Desa documents and interviews with informants involved in planning, budgeting, and decision-making processes. The analysis applies the Institutional Analysis and Development (IAD) framework to identify action arenas, actor positions, rules, resources, and choices that shape priority-setting decisions. The findings show that priorities established through village-level deliberations, including hamlet meetings, village meetings, and village development planning forums, do not automatically become budgetary decisions. During the preparation of the APB Desa, priorities undergo filtering and adjustment due to budget ceilings, regulations governing Village Fund utilization, external policy agendas, actor considerations, and administrative and technical requirements. The study proposes priority reconstruction as an analytical concept for explaining institutional adaptation as priorities move from the planning arena to the budgeting arena.